The Theological Implications of the Council’s Liturgical Constitution: Changes in the Concept of the Sacrament of Anointing of the Sick - Różycki, Ignacy (Studia Theologica Varsaviensia, 2020)
The Theological Implications of the Council’s Liturgical Constitution: Changes in the Concept of the Sacrament of Anointing of the Sick.